Advances in Biomaterials Science and Biomedical Applications 2013
DOI: 10.5772/53542
|View full text |Cite
|
Sign up to set email alerts
|

Cell Adhesion to Biomaterials: Concept of Biocompatibility

Abstract: According to Oudet [7], polymers have different physical properties. The most important are their thermal conductivity reflecting polymers' behaviour under temperature changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 54 publications
3
64
0
Order By: Relevance
“…7,8 Some cells prefer to attach to hydrophilic surfaces, while others have characteristic attraction towards hydrophobic ones. [20][21][22] Generally, hydrophobic surfaces are considered to be more protein-absorbent than hydrophilic ones, due to the strong hydrophobic interactions. 9,23 However, this could cause conformational changes or, sometimes, denaturation of proteins and, thus, lower the proliferation of cells on such surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Some cells prefer to attach to hydrophilic surfaces, while others have characteristic attraction towards hydrophobic ones. [20][21][22] Generally, hydrophobic surfaces are considered to be more protein-absorbent than hydrophilic ones, due to the strong hydrophobic interactions. 9,23 However, this could cause conformational changes or, sometimes, denaturation of proteins and, thus, lower the proliferation of cells on such surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure , it is possible to note that aluminium foils are characterized by a much higher roughness compared with silicon. It is well known that the presence of surface irregularities enhances the cell adhesion to substrates . In contrast to Si samples, aluminium surfaces did not show any sign of RA adsorption.…”
Section: Resultsmentioning
confidence: 70%
“…Contrary to the silicon polished substrates, aluminium foils have a relatively rough surface, which promotes cell adhesion . On the other hand, this feature makes the visualization of the cell morphology more complicated in comparison with the smoother silicon surface.…”
Section: Resultsmentioning
confidence: 99%
“…24 It is closely related with the surface charge effect because most of mammalian cells and their microenvironment including adhesion proteins known to negatively charged, and inhibited to adhere on negatively charged surface. 35,36 ECM proteins such as fibronectin and collagen would mediate cell attachment and proliferation by providing favorable surface charge compared to uncoated surface. 37 Our result demonstrated that cancer cells were not effectively attach and spread on negatively charged uncoated gold electrode surface because enough electrostatic binding between cells and negatively charged surface was not created to generate detectable impedance value upon cell attachment.…”
Section: Surface Properties Effects On Cell Growthmentioning
confidence: 99%